Fabrication of Nano-Silver Composite Using Amomum longiligulare Fruit Polysaccharides and Their Biological Activities - Lian Y; Ma N; Cheng Q; Luo M; Xu Z; He F; Zhou X; Zhang Y; Jin D; Kong Y; Wang Y; Wei N (International Journal of Nanomedicine)
Yong Lian,1,* Ning Ma,2,* Qianying Cheng,1,* Mingquan Luo,1 Zhen Xu,1 Fei He,1 Xiaomei Zhou,1 Ying Zhang,1 Dejun Jin,1 Yidan Kong,1 Yong Wang,1 Na Wei1 1Hainan Provincial Key Laboratory of R&D on Tropical Herbs, Engineering Research Center of Tropical Medicine Innovation and Transformation of Ministry of Education, International Joint Research Center of Human-Machine Intelligent Collaborative for Tumor Precision Diagnosis and Treatment of Hainan Province, School of Pharmacy, Hainan Medical University, Haikou, 571199, People’s Republic of China; 2Reproductive Medical Center, Hainan Women and Children’s Medical Center, Haikou, Hainan Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Na Wei; Yong Wang, Hainan Provincial Key Laboratory of R&D on Tropical Herbs, School of Pharmacy, Hainan Medical University, Haikou, 571199, People’s Republic of China, Email weina-0613@163.com; wangyong1982_2004@163.comPurpose: Study aims to optimize the synthesis conditions for silver nanoparticle composites [ALP(D)-AgNPs] using a rapid and environmentally friendly method and investigate the antioxidant, antibacterial, and anticancer activities of the fabricated composite.Methods: The polysaccharide component ALP-D was extracted and purified from the fruits of Amomum longiligulare and subsequently used for further experiments. The structure of ALP-D was characterized by FT-IR, monosaccharide composition and molecular weight.The optimal conditions for the green synthesis of silver nanoparticles using ALP-D were determined through single-factor experiments. The synthesized silver nanoparticles were characterized by UV-Vis spectroscopy, FT-IR, DLS, HRTEM and XRD. Finally, the in vitro antioxidant activity, antibacterial activity and anticancer activity of the nano-silver composite were evaluated.Results: Single-factor experiments identified the optimal synthesis conditions for ALP(D)-AgNPs as a reaction time of 180 min, a temperature of 100 °C, and a 10:1 volume ratio of silver nitrate to ALP-D. The free radical scavenging activity of ALP(D)-AgNPs against DPPH and ABTS was significantly enhanced compared with that of ALP-D. The minimum inhibitory concentration (MIC) values of ALP(D)-AgNPs against E coli and B subtilis were 31.25 μg/mL, while the MIC value against S aureus was 62.5 μg/mL. The minimum bactericidal concentration (MBC) values of ALP(D)-AgNPs were 125 μg/mL for E coli, B subtilis, and S aureus. The IC50 values of ALP(D)-AgNPs on the MDA-MB-231, HepG2, Caco-2, and C6 cancer cell lines were 14.72 ± 0.23, 8.19 ± 0.65, 22.73 ± 3.01, and 15.77 ± 2.91 μg/mL, respectively.Conclusion: In summary, we have identified a novel material for the green synthesis of silver nanoparticles. The results show the ALP(D)-AgNPs synthesized using the new material ALP-D exhibit excellent stability and dispersibility. Furthermore, the biological activity reveals that ALP(D)-AgNPs possess notable antioxidant, antibacterial, and cancer-suppressing activities.Keywords: ALP-D, ALP(D)-AgNPs, antioxidant activity, antibacterial activity, anticancer activity